Cryptococcosis in the era of AIDS--100 years after the discovery of Cryptococcus neoformans. - Mitchell, T G (1995)
Although Cryptococcus neoformans and cryptococcosis have existed for several millennia, a century has passed since the discovery of this encapsulated yeast and its devastating disease. With the advent of the AIDS pandemic, cryptococcal meningitis has emerged as a leading cause of infectious morbidity and mortality and a frequently life-threatening opportunistic mycosis among patients with AIDS. Both basic and clinical research have accelerated in the 1990s, and this review attempts to highlight some of these advances. The discussion covers recent findings, current concepts, controversies, and unresolved issues related to the ecology and genetics of C. neoformans; the surface structure of the yeast; and the mechanisms of host defense. Regarding cell-mediated immunity, CD4+ T cells are crucial for successful resistance, but CD8+ T cells may also participate significantly in the cytokine-mediated activation of anticryptococcal effector cells. In addition to cell-mediated immunity, monoclonal antibodies to the major capsular polysaccharide, the glucuronoxylomannan, offer some protection in murine models of cryptococcosis. Clinical concepts are presented that relate to the distinctive features of cryptococcosis in patients with AIDS and the diagnosis, treatment, and prevention of cryptococcosis in AIDS patients.